1996
DOI: 10.1159/000289085
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Difficulties of Facial Expression of Emotions in Mothers of Children Suffering from Developmental Obesity

Abstract: Background: The relationship between developmental obesity and emotional problems has been particularly studied by Bruch. According to this author, the main reason for early-onset obesity has to be found in the difficulty of some mothers to adequately distinguish between emotional manifestations and the child’s real need for food. In this paper an experiment was carried out in order to test the relationship between developmental obesity and poor ability to recognize facial expressions of some basic emotions. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…These results are consistent with a previous study, 8 which found a reduced ability to recognize posed expressions of emotions in obese children and in their mothers; in addition, they indicate that the deficit involves both visual cues and nonverbal vocal cues. The intensity of the expression of the emotions and the facilitation of the task, because of the contemporary presence of the visual and vocal cues, did not affect the difference in performance between the obese and the comparison group.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with a previous study, 8 which found a reduced ability to recognize posed expressions of emotions in obese children and in their mothers; in addition, they indicate that the deficit involves both visual cues and nonverbal vocal cues. The intensity of the expression of the emotions and the facilitation of the task, because of the contemporary presence of the visual and vocal cues, did not affect the difference in performance between the obese and the comparison group.…”
Section: Discussionsupporting
confidence: 93%
“…Clashing with the needs of her child is extremely stressful for a mentally ill mother, but that can usually be overcome through the support of the ward staff, both in everyday matters and emotionally [3, 5, 6,21,22,23,24]. The prerequisite for this is a pre-existing infrastructure in the hospital [3].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the effect may be illustrated by aberrations of social-emotional prosody disrupting maternal communications with their infants [97]. Notably, children suffering from serious obesity and their mothers show a reduced ability to decode nonverbal expression of emotions [98].…”
Section: The Fox or The Hedgehog Strategy?mentioning
confidence: 99%